Penilaian Otomatis di SMK TI Budi Agung dengan Certainty Factor - Alfina, Ommi (Universitas Methodist Indonesia, 2025)
The assessment system at SMK TI Budiagung still relies on conventional methods but has gradually shifted towards AI-based automated assessment. This study aims to analyze the effectiveness of an automated assessment system using the Certainty Factor method in evaluating students objectively and accurately. The research methodology includes interviews with educators and an analysis of the implemented system. The findings indicate that automated assessment enhances efficiency in grading objective answers but faces challenges in evaluating subjective aspects such as creativity and problem-solving skills. Furthermore, the application of the Certainty Factor method allows the system to provide assessments based on calculated certainty levels from available data. The main challenge is ensuring valid and weighted data for more accurate evaluation results. With further development and integration into the learning system, automated assessment is expected to improve academic evaluation quality at SMK TI Budiagung.